2022
DOI: 10.21873/invivo.12951
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes in Major Salivary Glands in Mice Treated With a Choline and Methionine Deficient Diet

Abstract: Background/Aim: It has been shown that the methionine-choline deficient (MCD) diet induces hepatocarcinogenesis, but not in extrahepatic organs, such as the testis, and pancreas, although may increase chemicalinduced carcinogenesis in the colon, mammary gland, esophagus, and pancreas. Accumulating evidence suggests that salivary glands are very susceptible to stress conditions, such as radiation, hyperglycemia, and exposure to xenobiotics in vivo. This study aimed to analyze the histological changes on the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(32 reference statements)
0
0
0
Order By: Relevance
“…However, to the best of our knowledge, no study has reported the effects of combination therapy with liraglutide and metformin on NASH. In this study, we used a methionine/choline-deficient (MCD) diet-fed C57BL/6JNarl mouse model to study the combined effects of liraglutide and metformin on NASH (33,34).…”
mentioning
confidence: 99%
“…However, to the best of our knowledge, no study has reported the effects of combination therapy with liraglutide and metformin on NASH. In this study, we used a methionine/choline-deficient (MCD) diet-fed C57BL/6JNarl mouse model to study the combined effects of liraglutide and metformin on NASH (33,34).…”
mentioning
confidence: 99%